A new species of Philonthus (Coleoptera: Staphylinidae) from Sonora, México - Navarrete-Heredia, José Luis (Zootaxa, 2003)
Philonthus yaqui sp. nov. is described based on 51 specimens collected in Yécora, Sonora, México. A key for recognition of this species and those close related from México and the United States is provided.